EVALUASI HASIL PROGRAM JAMINAN KESEHATAN DAERAH DI KABUPETEN SEMARANG TAHUN 2013 - Andri Setiawan; Kismartini Kismartini; Dewi Rostyaningsih (Journal of Public Policy and Management Review, 2015)
Membership of Jamkesda Program in Semarang Regency that did not increase since the very first time it was out, moreover a big number of decrease of the coverage membership of Jamkesda Program in 2012, has became a background and reason for this research, because in 2013 was the last time the Jamkesda Program is fully implemented. The goal of this research is to explain the output of the Jamkesda Program in Semarang Regency in 2013 and the factors that influence it. The ways to solve this problem and its goal is done by using systematic-analysis theory with using effecttivity. The object of this research is The Health Department as the administrator of the Jamkesda Program, the citizen who get the membership of the program, and Health Service officer. The results show that in the output dimensions related to the effectiveness of membership of Jamkesda Program has not been achieved because there are still some low income citizen who haven’t receive the membership. The dominant factor that because the based of the problem is the incomplete ID (Identity Card) of citizenship. Beside the use of SKTM as a solution to an issue also was not effective. Beside that the services to member of Jamkesda also not been effective because of the imbalance between health care giver. The dominant factor is selected based referral personal wishes. It was suggested that regarding the problem of membership, The Health Department as the administrator of the program to cooperate more with the villager. The limitations of Health Care Providers should be stipulated